PENGARUH KOMPENSASI TERHADAP KUALITAS PELAYANAN PUBLIK DINAS KESEHATAN KOTA MANADO - SITEPU, CITRA MAHARANI; LENGKONG, FLORENCE D.J. LENGKONG DAICY; LONDA, VERY (Sam Ratulangi University, 2018)
bstract: Fair compensation and acceptable to employees will encourage employees to work better andaffect the quality of public service Manado City Health Office. This study aims to determine and analyse thedevelopment of public service quality in Manado City Health Office.Method of taking data in this research using survey by using questionnaire. Data analysis techniquesthat are simple regression analysis and simple analysis. The result of simple linear regression analysis wasassessed by regression coefficient (b) with positive sign that is 0,952 and acquisition of constant value (a)equal to 9,999. Then the equation is Y = 9,999 + 0.952. Based on the results of analysis and Pearson productmoment obtained locked coefficient (r) of 0.698 with the coefficient of determination (r2) of 0.488. Theresult shows that the variable of openness to the quality of public service is equal to 48.8% in accordancewith Public Service Quality, which is one of the variables taken by the respondents. By providing fair andreasonable compensation will affect and improve the quality of public services in Manado City HealthOffice.Keywords: Compensation, Quality of public service